2018
DOI: 10.1080/08927936.2018.1483870
|View full text |Cite
|
Sign up to set email alerts
|

Roaming Companion Cats as Potential Causes of Conflict and Controversy: A Representative Questionnaire Study of the Danish Public

Abstract: Cats have grown in popularity as companion animals, but there are also people who strongly dislike them. Companion cats allowed to roam freely outdoors are seen by some as a nuisance. This paper, drawing on research conducted in Denmark, aims to quantify potentially conflicting attitudes to cats among the public that may feed into cat-related conflicts and controversies. Questionnaire data were collected from a representative sample of the Danish population (n = 2,003), where 21% (n = 415) owned cats and 79% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…As the cat gains greater popularity as a companion animal [10,11], there is increasing need for knowledge about the human-cat relationship and how it affects cats' behavior and welfare [12,13]. There is a belief that cats can easily cope with the owners' absence for long periods of time and few studies have been conducted to support that assumption [14].…”
Section: Introductionmentioning
confidence: 99%
“…As the cat gains greater popularity as a companion animal [10,11], there is increasing need for knowledge about the human-cat relationship and how it affects cats' behavior and welfare [12,13]. There is a belief that cats can easily cope with the owners' absence for long periods of time and few studies have been conducted to support that assumption [14].…”
Section: Introductionmentioning
confidence: 99%
“…A Danish study found that most of the population, about 60%, did not see a problem with allowing cats to roam freely, while about 27% did consider them to be an issue [80]. The other 13% in this study had no opinion on the topic.…”
Section: Perceptions Around Feral Cats and Their Managementmentioning
confidence: 62%
“…The other 13% in this study had no opinion on the topic. Most of the people who did consider roaming cats to be a problem had never had a cat for a pet, and those that had were more likely to accept the free roaming of cats [80]. Though perhaps not directly labelled as feral cats in the study, the sentiment of non-cat owners expressing stronger dislike for roaming cats may present a common theme in studies of perception around feral cats and their management, and should be carefully considered [80].…”
Section: Perceptions Around Feral Cats and Their Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Selecting the appropriate message framing, i.e., how the issue is presented, is an important consideration [71,72]. Many target audiences of free-roaming cat communications have strongly held beliefs and attitudes on the subject [41,73,74,75,76,77]. Using frames that match audience values and concerns will get the message noticed, processed and acted upon [72,78].…”
Section: Development Of Interventionsmentioning
confidence: 99%